Investigating the associations between personality functioning, cognitive biases, and (non-)perceptive clinical high-risk symptoms of psychosis in the community - Rinaldi, Giulia; Lerch, Stefan; Schultze-Lutter, Frauke; Schmidt, Stefanie Julia; Cavelti, Marialuisa; Kaess, Michael; Michel, Chantal (European psychiatry, 2025)
Background. Beyond psychosis prediction, clinical high-risk (CHR-P) symptoms show clinical relevance by their association with functional impairments and psychopathology, including personality pathology. Impaired personality functioning is prioritized in recent dimensional personality disorder models (DSM-5, ICD-11), yet underexplored in CHR-P, as are associations with cognitive biases, which early studies indicate as possibly linking CHR-P-symptoms and personality pathology. Methods. A community sample (N = 444, 17–60 years, 61.8% female) was assessed via clinical telephone interview and online questionnaires. Using zero-inflated Poisson models, we explored associations of personality functioning, cognitive biases, current psychopathology, and psycho-social functioning with likelihood and severity of overall CHR-P, as well as perceptive (per-) and non-perceptive (nonper-)CHR-P-symptoms distinctly. Results. Higher nonnper-CHR-P-symptom likelihood was associated with more impaired personality functioning and psychosocial functioning, while more severe cognitive biases were associated with higher CHR-P- and per-CHR-P-symptom likelihood, alongside higher CHR-P- and nonper-CHR-P-symptom severity. Further, more axis-I diagnoses were linked to higher CHR-P-, per-CHR-P-, and nonper-CHR-P-symptom likelihood, and younger age to higher CHR-P- and per-CHR-P-symptom severity, with CHR-P-symptom severity appearing higher in females. In an exploratory analysis, personality functioning elements identity and self-direction, and cognitive biases dichotomous thinking, emotional reasoning, and catastrophizing, respectively, showed multifaceted associations with nonper-CHR-P-symptom likelihood and overall CHR-P-symptom expression. Conclusions. Our study supports the association of CHR-P-symptoms with multiple mental health factors. Findings suggest intricate associations between personality functioning impairments and cognitive biases with CHR-P-symptom expression in non-help-seeking populations, possibly contributing to different per-CHR-P- and nonper-CHR-P-symptom expression patterns. Therefore, they should be targeted in future longitudinal studies, aiming at better understanding CHR-P-manifestations to inform preventive intervention.
Gesehen am 18.08.2025